2012
DOI: 10.1002/jcb.23427
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the specificity of protease‐activated receptors 1 and 2 signaling by factor Xa and thrombin

Abstract: Factor Xa (FXa) elicits intracellular signaling responses through the activation of protease-activated receptor 2 (PAR2) and possibly also through PAR1 in endothelial cells. In this study, we investigated FXa signaling in endothelial cells when the protease was either in free form or assembled into the prothrombinase complex. Furthermore, we prepared several wild-type and mutant PAR1 and PAR2 cleavage-reporter constructs in which their exodomains were fused to cDNA encoding for a soluble alkaline phosphatase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 35 publications
6
32
1
Order By: Relevance
“…In addition to their essential role in blood clotting, both factor Xa and thrombin can elicit multiple cellular effects via PARs and their co-receptors. Thrombin activates PAR1, whereas factor Xa can also signal via PAR2, directly or together with the TF–factor VIIa complex 122,123,126 . Consistent with these observations, inhibition of factor Xa but not of thrombin suppressed expression of the proinflammatory cytokine IL-6, emphasizing the beneficial effects of protease-specific inhibition in a mouse model of sickle cell disease 123 .…”
Section: Effect Of Anticoagulation On Renal Functionmentioning
confidence: 99%
“…In addition to their essential role in blood clotting, both factor Xa and thrombin can elicit multiple cellular effects via PARs and their co-receptors. Thrombin activates PAR1, whereas factor Xa can also signal via PAR2, directly or together with the TF–factor VIIa complex 122,123,126 . Consistent with these observations, inhibition of factor Xa but not of thrombin suppressed expression of the proinflammatory cytokine IL-6, emphasizing the beneficial effects of protease-specific inhibition in a mouse model of sickle cell disease 123 .…”
Section: Effect Of Anticoagulation On Renal Functionmentioning
confidence: 99%
“…In this study, a peptide mimicking this FXa amino acid sequence (FX 83-88 ), previously shown to be crucial for PAR2-dependent barrier protective and anti-inflammatory activity of FXa on endothelial cells, 22,23 produced a dose-dependent decrease in FXa regulation of LPS-stimulated cytokine production from THP-1 cells, such that FXa anti-inflammatory activity could be completely blocked by the presence of this peptide. Interestingly, bovine FXa, whose inter-EGF region amino acid sequence is not similar to its human counterpart, was unable to mount an anti-inflammatory response similar to that of human FXa, providing a possible explanation for the observed species-specific loss of function.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the FXa Gla domain may not be required for PAR2-dependent FXa signaling on endothelial cells. 22 It is not clear at this stage whether FXa Gla domain truncation confers long-range structural changes that disrupt FXa myeloid receptor binding sites on the Gla domainless protease, or itself represents a crucial binding site for FXa myeloid cell surface receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it is the suppression of the anticoagulants PC and AT that allows for the continued formation of the procoagulant complexes by not inactivating FVa and FVIIIa, which converts FX to FXa and allows for the continuation of thrombin generation. The increase in these critical enzymes (FXa and thrombin) also further promotes the observed hypercoagulation in part through the activation of protease‐activated receptors 1 and 2,55, 56, 57 which is seen in this population by the increased proinflammatory cytokines such as IL‐6. This combined effect may be driving the excess thrombin generation that is seen among the mortality cases.…”
Section: Discussionmentioning
confidence: 98%